Modelization of electrical and optical characteristics of short-wave infrared type I InGaAsBi/InGaAs/InP quantum wells p-i-n detector. (29th December 2020) - Sfina, N; Ammar, I; Lazzari, J-L; Said, M
Abstract: In the present work, we will exhibit a theoretical analysis and optimization of electrical and optical characteristics of a short-wave infrared p-i-n detector closely lattice matched to conventional (001) InP substrate by the use of quaternary dilute bismide alloy Inx Ga1−x As1−y Biy /Inx Ga1−x As quantum wells as an active layer. The content of about 6% of Bismuth has been responsible of red-shift of the 50% cut-off wavelength from 2.2 towards 2.8 μ m at room temperature, resulting in a band gap reduction of nearly 305 meV caused by the bismuth incorporation. The temperature dependence of zero-bias resistance area product ( R 0 A ) and bias dependent dynamic resistance of the designed structure have been investigated thoroughly to analyses the dark current contributions mechanisms that might limit the electrical performance of the considered structure. It was revealed that the R 0 A product of the detector is limited by thermal diffusion currents when temperatures are elevated whereas the ohmic shunt resistance contribution limits it when temperatures are low. The modeled heterostructure, reveals a comforting dark current of 1.25 × 10 −8 A at bias voltage of −10 mV at 300 K. The present work demonstrates that the p-i-n detector based on compressively strained Inx Ga1−x As1−y Biy quantum well is a potential candidate for achieving a short-wave infrared detection.